2010
DOI: 10.1242/jcs.072124
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides differentially regulate bacterial uptake and Nramp1-induced resistance toLegionellainfection inDictyostelium

Abstract: SummaryMembrane phosphatidylinositides recruit cytosolic proteins to regulate phagocytosis, macropinocytosis and endolysosomal vesicle maturation. Here, we describe effects of inactivation of PI3K, PTEN or PLC on Escherichia coli and Legionella pneumophila uptake by the professional phagocyte Dictyostelium discoideum. We show that L. pneumophila is engulfed by macropinocytosis, a process that is partially sensitive to PI3K inactivation, unlike phagocytosis of E. coli. Both processes are blocked by PLC inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 86 publications
8
91
0
Order By: Relevance
“…The nramp1 gene (DDB_G0276973) is the ortholog of mammalian nramp1 and was characterized previously (Peracino et al, 2006;Peracino et al, 2010). The nramp2 gene (DDB_G0275815) encodes a putative integral membrane protein with 12 transmembrane domains and a M r of 70 kDa, 10 kDa larger than Nramp1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The nramp1 gene (DDB_G0276973) is the ortholog of mammalian nramp1 and was characterized previously (Peracino et al, 2006;Peracino et al, 2010). The nramp2 gene (DDB_G0275815) encodes a putative integral membrane protein with 12 transmembrane domains and a M r of 70 kDa, 10 kDa larger than Nramp1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…How can inactivation of Nramp2, which is localized in the contractile vacuole, have a similar effect, if Nramp1 is active? We have recently shown that Legionella effectively hinders recruitment of the V-H + -ATPase, but not Nramp1, to the Legionella-containing macropinosome (Peracino et al, 2010). In the absence of the vacuolar ATPase, Nramp1 pumping activity is neutralized, and iron may be sequestered by the Legionella (Peracino et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Confocal series images were taken as described previously (Peracino et al, 2010;Buracco et al, 2015).…”
Section: Fluorescence Microscopy Imagingmentioning
confidence: 99%